PHASES and the natural history of unruptured aneurysms: science or pseudoscience? - Rinkel, Gabriel J. E.; Etminan, Nima (Journal of neuroInterventional surgery, 2017)
We thank Dr Darsaut et al 1 for their attention paid to the PHASES score and for sharing their thinking in an opinion paper 2 years after the publication of our article.2 The authors discuss whether or not prediction modeling based on data from previous observational studies is science. Their final conclusion is that the only valid way to decide whether or not unruptured aneurysms should be treated is to compare outcomes in patients eligible for both options (ie, aneurysm occlusion …
Published online first 18 April 2016
Gesehen am 26.06.2018